KONSEP 4 M (MENGETAHUI, MENCINTAI, MENGINGINKAN, MENGERJAKAN) PENDIDIKAN KARAKTER PERSPEKTIF RATNA MEGAWANGI DAN RELEVANSINYA DALAM MENCIPTAKAN AKHLAK (STUDI KASUS DI MTs N 1 PALEMBANG) - Fina Badriyah; Akmal Hawi; Muhammad Fauzi (PAI RAFAH, 2021)
Character education and moral education are values education that both emphasize the importance of a process. Therefore, both prioritize and prioritize lengthy practice and habituation. In a long and continuous training process, a child is given freedom and opportunity to be able to understand, feel and predict good actions. As with the policy carried out by the MTs Negeri 1 Palembang school in creating student morals through habituation, which is shown from several school activities. One of the character education leaders in Indonesia, Ratna Megawangi, also offers a method for character formation, namely the concept of 4 M (knowing, loving, desiring, acting) the good continuously. So, how exactly is the reliance between the concepts introduced by Ratna Megwangi and the process of creating the morals of students at MTs Negeri 1 Palembang.The type of research used is the type of case study research. The research approach is using a qualitative approach. Furthermore, the method of data collection is done by observing methods, interviews, documentation, library research. Data analysis techniques by data reduction, data presentation and data verification.The results obtained are the concept of 4 M (Knowing, Loving, Desiring, Acting) character education Ratna Megawangi has a relevance in creating student morals at MTs Negeri 1 Palembang. As a statement from one of the informants said that the concept or method introduced by Ratna Megawangi is quite relevant in the process of creating student morals, because character or character cannot be shaped if it is through a theoretical learning process, but must involve other aspects such as emotions, cognitive, affective, psychomotor. Student character education is a process for carving morals through the process of knowing goodness, loving kindness, wanting goodness and doing good. It shows an educational process that involves cognitive, affective and psychomotor aspects, so that noble character can be engraved into a habit of mind, heart and hands.